Local self-government in the focus of the medical reform in Ukraine: analysis of powers - Khozhylo, Iryna; Nadyuk, Zinoviy; Antonova, Olga; Tarasenko, Tetiana; Serohina, Tetiana (My University, 2020)
This article considers power distribution issues in scientific discourse and searches for available solutions to implement by local authorities in the field of healthcare in the conditions of authority decentralization. Importance of solving this scientific issue lies in the fact that not all communities have financial capacity to maintain on their own a network of medical institutions, since most of Ukrainian regions are financially depressed, and before the reform the network of social facilities (schools, houses of culture, clinics) had been funded through subsidies from the budget of a higher level. The network of financial institutions that are subject to reformation and are owned by local communities at present totals around 10,000 all over Ukraine, which demands for an incremental implementation of structural and functional changes (pilot start of reforms, active phase, reformation completion). Desk research method and secondary analysis of literary, research and analytical sources and regulatory methods have been selected as methodological tools for the conducted research. The research period covers years 1991 through 2019. The object of the research is power of local self-governments (their own as well as delegated), since almost 80% of medical services are provided on the territorial community level. The article presents results of empirical analysis regarding distribution of financial power in the new model of healthcare management, which proves that in its essence it remained budget-funded, as it had been before the reform. The research empirically confirms and theoretically proves that the course of reforms, in general, has been chosen correctly, and the first conclusions of international experts also give positive assessment of the reform management. Results of the conducted research can be useful to local authorities, who directly represent the interests of territorial communities, and local executive authorities involved in implementation of these reforms and declaring their interest in Ukraine’s commitment to the course towards European integration changes.
Keywords: local self-government; medical reform; powers